Role of network competence on entrepreneurship growth in small and medium enterprises - Eze, Kingsley Ezuma; Ismail, Maimunah (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This is an extensive review paper which proposes a conceptual model relating network competence on entrepreneurship growth in the manufacturing sector of small and medium sized enterprises (SMEs). The authors reviewed past research on network competence and entrepreneurship growth through such key words as network competence, human resource development, manager’s qualification, task performance and entrepreneurship growth in the SMEs. Four predictors of SMEs growth were identified, including availability of resources, network orientation of human resource management, integration of communication system, openness to corporate culture. These findings are linked with entrepreneurship growth in the SMEs while a number of prepositions are offered to explain the proposed model of entrepreneurship growth in the SMEs from the perspective of network competence. This paper offers practical interventions for human resource development (HRD) managers to assist SMEs linked firm towards developing and managing networking competence to ensure entrepreneurship growth of the SMEs in the manufacturing sector. It also highlights the relevance of HRD tools, in developing and improving the skills and qualification of a manager, to perform networking task in the SMEs. This paper contributes to literature on the significance of network competence in managing and promoting growth in the SMEs.